Analysis of Dynamic Performance for Compound Pendulum Jaw Crusher with Bearing Clearance - Jiang Zhihong; Zhang Chengkun (Jixie chuandong)
The clearance between the eccentric shaft and the bearing of the movable jaw axle is neglected in previous studies on the dynamic performance of complex pendulum jaw crushers. Aiming to the impact of the bearing clearance on the dynamic performance of complex pendulum jaw crushers, a dynamic model of a complex pendulum jaw crusher with bearing clearance is established using the Lagrange multiplier method. Its correctness is verified through experiments, and the effects of different eccentric shaft speeds and clearance values on the dynamic performance of the crusher are analyzed. The results indicate that increasing the eccentric shaft speed and reducing the clearance value can improve the dynamic performance of the crusher, enhance its operational stability, and extend the bearing life. Increasing the eccentric shaft speed can also reduce irregular wear of the bearings. For the PE150×250 jaw crusher, in order to improve productivity while reducing the impact phenomenon within the crusher, a speed of 38 rad/s is considered optimal.